A Novel Tibial Precut Technique for Varus Deformity Correction in Transfibular Total Ankle Arthroplasty: A Technical Tip - Koichiro Yano MD, PhD; Katsunori Ikari MD, PhD; Masataka Kakihana MD, PhD; Yuki Tochigi MD, PhD; Ken Okazaki MD, PhD; Lew C. Schon MD (Foot & Ankle Orthopaedics, 2025)
Graphical Abstract